Tập I - Đập dàn cọc (giải pháp công nghệ tạo nguồn nước vùng ven biển) - Trương, Đình Dụ (2011)
Tác giả: Trương Đình Dụ, GS, PTS; Vũ Văn Thăng, PTS; Vũ Đình Hùng, ThS; Vũ Hồng Sơn, KS; Phạm Kim Thoa, KS; Nguyễn Quốc Dũng, KS; Nguyễn Thành Công, KS -- Từ khóa: Đập; Dàn cọc; Ngăn sông; Thi công